Drivers of chaparral type conversion to herbaceous vegetation in coastal Southern California. Issue 1 (31st August 2018) - Syphard, Alexandra D.; Brennan, Teresa J.; Keeley, Jon E.
Abstract: Aim: In Southern California, native woody shrublands known as chaparral support exceptional biodiversity. However, large‐scale conversion of chaparral into largely exotic herbaceous cover is a major ecological threat and serious conservation concern. Due to substantial uncertainty regarding the causes and extent of this vegetation change, we aimed to quantify the primary drivers of and map potentially vulnerable locations for vegetation type conversion from woody into herbaceous cover. Location: Santa Monica Mountains National Recreational Area, Southern California, USA. Methods: We used air photograph image interpretation to quantify the extent to which chaparral shrublands transitioned to herbaceous cover from 1943 to 2014 across nearly 800 randomly located plots. Comparing plots that remained chaparral to those that converted to herbaceous cover, we performed hierarchical partitioning to quantify the independent contribution of a range of explanatory variables, and then used classification trees to explore variable interactions. We also developed a spatial model to create a seamless map delineating relative probability of type conversion. Results: Of the original plots that were chaparral in 1943, 284 (36%) changed cover by 2014, with 79 completely converting, and 142 mostly converting to herbaceous cover. The primary mechanism behind shrubland decline and replacement was short intervals between fires (<=10 years), and type conversion was most likely to occur in arid parts of the landscape with low topographic heterogeneity and close proximity to trails and roads. Predictive maps delineated several hotspots with environmental conditions similar to those of type‐converted plots. Main conclusions: Chaparral type conversion is a widespread conservation concern, and results here suggest that short‐interval fire and landscape disturbance are the most likely factors to exacerbate it, particularly in water‐limited portions of the landscape where chaparral is subject to greater physiological stress and slower recovery. Reducing fire ignitions and mapping vulnerable areas may be important strategies for prevention.